Canary Islands burned land mapping using MODIS and HOTSPOT data - Huesca, M.; González-Alonso, F.; Cuevas, J. M.; Merino-de-Miguel, S. (Forest Systems, 2008)
This study presents a rapid, accurate and economic methodology for forest fire burned areas estimation using remote sensing techniques. The algorithm used is based on thresholds identifications from infrared spectral band, using MODIS images and hotspots time series delivered from NASA. The threshold is defined by the maximum correlation between the infrared band and hotspot influence area. The results show the usefulness of the presented methodology in forest fire burned area estimation and its relevance for prioritizing forest management activities and for planning future reforestations work in the affected area.